Double outlet right ventricle - Yolandee Bell-Cheddar; Yolandee Bell-Cheddar; William A. Devine; Carlos-Eduard; Laura Seese; Mario Castro-Medina; Raymond Morales; Christopher W. Follansbee; Tarek Alsaied; Jiuann-Huey I. Lin; Jiuann-Huey I. Lin (Frontiers Media S.A., 2023)
This review article addresses the history, morphology, anatomy, medical management, and different surgical options for patients with double outlet right ventricle.